2020
DOI: 10.1002/admt.202000494
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Stretchable OLEDs: A Hybrid Platform Based on Rigid Island Arrays on a Stress‐Relieving Bilayer Structure

Abstract: Optoelectronic devices that are stretchable can revolutionize various fields by enabling the functionalities that are not accessible from conventional rigid platforms. In this respect, many efforts are made to realize stretchable organic light‐emitting diodes (OLEDs) for their compatibility with various deformable substrates. Two representative examples of such efforts include a method based on intrinsically stretchable materials and a method to attach ultrathin OLEDs on a prestrained elastomer substrate. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
(19 reference statements)
0
26
0
1
Order By: Relevance
“…Through structural engineering, stretchable LED arrays using rigid EL devices can be developed. [74][75][76][77] Although each lightemitting unit is not flexible, the entire array can be stretched using submillimeter-size LEDs and stretchable interconnection. During mechanical deformation, the interconnects are deformed instead of LEDs and release the stress applied to the device, avoiding mechanical failures.…”
Section: Ultrathin El Devices With Island-bridge Structuresmentioning
confidence: 99%
“…Through structural engineering, stretchable LED arrays using rigid EL devices can be developed. [74][75][76][77] Although each lightemitting unit is not flexible, the entire array can be stretched using submillimeter-size LEDs and stretchable interconnection. During mechanical deformation, the interconnects are deformed instead of LEDs and release the stress applied to the device, avoiding mechanical failures.…”
Section: Ultrathin El Devices With Island-bridge Structuresmentioning
confidence: 99%
“…The luminance at a constant 6.5 V decreased by 19% after 1000 repeated stretch-release cycles between 0 and 20% strain. Kim et al [38] took a different approach for stress relief where a thick ultrasoft silicone elastomer layer (Silbione; Young's modulus ≈ 0.9 kPa) was inserted in between PDMS substrate and SU-8 layer (Figure 3h). Their experiment results showed that the maximum stretchability of the interconnects was increased from 170% to 350% as the modulus of Silbione was decreased from >10 to 0.9 ± 0.02 kPa.…”
Section: Island-bridge Structurementioning
confidence: 99%
“…i) Photograph of stretchable OLED where 140% maximum stretchability for the interconnects was demonstrated. Reproduced with permission [38]. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%
“…SU-8, polyimides, etc.) [2]. The elastomer substrates basically limit the overall degree of stretching capability and provide straightforward handling.…”
Section: Design Considerations For Deformable Oledsmentioning
confidence: 99%
“…Therefore, it is not necessarily trivial to realize working organic devices with such various form factors. In this work, we will first address key issues in forming deformable organic lightemitting diodes (OLEDs) with case studies done for ultrathin and stretchable OLEDs [1,2]. In addition, we present OLEDbased wearable healthcare applications such as OLED-based pulse oximetry sensors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%